2014
DOI: 10.1590/0103-166x2014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Breathing and relaxation training for patients with hypertension and stress

Abstract: This study evaluated the effects of the relaxation and breathing training for hypertensive patients on the index, levels and symptoms of stress and blood pressure among hypertensive patients suffering from stress. Nineteen patients from a hypertension and diabetes program in Rio de Janeiro participated in the study that which used, as instruments, Lipp's inventory of stress symptoms for adults, the psychological interview for hypertensive patients, the relaxation and breathing training for hypertensive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…This finding agreed with study by Chicayban and Malagris, as they found that stress management training for hypertensive patients has been identified as a beneficial strategy in controlling stress mainly and it may be helpful as a non-pharmacological strategy in the treatment of hypertension, however, it was not regarded as capable of significantly reducing SBP levels 14 .…”
Section: Discussion:-supporting
confidence: 91%
See 1 more Smart Citation
“…This finding agreed with study by Chicayban and Malagris, as they found that stress management training for hypertensive patients has been identified as a beneficial strategy in controlling stress mainly and it may be helpful as a non-pharmacological strategy in the treatment of hypertension, however, it was not regarded as capable of significantly reducing SBP levels 14 .…”
Section: Discussion:-supporting
confidence: 91%
“…By the end of our study, patients within intervention group reported statistically significant improvement in perceived stress scores and blood pressure control compared to patients within control group. This can be attributed to application of our intervention that also increases number of patients whom blood pressure became controlled Different studies agreed with our finding as they found that the relaxation response may contribute to a reduction in anxiety and other negative, psychological reactions attributable to stress [13][14] .…”
Section: Discussion:-supporting
confidence: 88%
“…The increase in peripheral vascular resistance and cardiac output, in an attempt to restore muscle blood flow, favors elevated blood pressure levels (Chicayban and Malagris, 2014). Studies show that it is possible to understand that altered posture, sustained for a long time, can stimulate the metaboreceptors of large muscle groups, such as tibialis anterior, triceps sural, and hamstrings, causing an increase in BP and a decrease in perfusion pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in these regions were also prominent in the modulation of diastolic pressure in the data of this study. Some resulting consequences are early muscle fatigue and decreased muscle performance, which are also associated with the changes existing during aging (Chicayban and Malagris, 2014;Goes et al, 2018). Our results agree with previous studies that showed that joint mobility of movement and postural change by stretching for 14 weeks effectively reduces blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Relaxation techniques have shown benefits for reducing blood pressure and stress levels in pregnant women with hypertension (Soliman, Elalem, & Elhomosy, 2017). There are also relaxation techniques that are combined with breathing techniques so that it gives an effect that is effective in controlling stress in hypertensive patients (Chicayban & Malagrisi, 2014).…”
Section: Physical Therapymentioning
confidence: 99%